A combined transient and steady state approach for robust lifetime spectroscopy with micrometer resolution. Issue 12 (22nd October 2015) - Heinz, Friedemann D.; Mundt, Laura E.; Warta, Wilhelm; Schubert, Martin C.
Abstract : We present the combination of two complementary micro‐photoluminescence spectroscopic techniques operating in transient and steady state condition, respectively. Introducing the time domain into the well‐established micro‐photoluminescence mapping approach operating under steady state conditions demonstrates a distinct improvement of the robustness and reliability in the determination of charge carrier lifetime measured with micrometer spatial resolution. Lifetimes from 50 ns to above ms are accessible. We elaborate a calibration procedure and apply the combined all‐photoluminescence setup to high‐performance multicrystalline silicon. A lifetime image obtained from the established photoluminescence imaging technique is reconstructed from the microscopic map by considering lateral diffusion and optical blurring, revealing a more detrimental influence of small angle grain boundaries as well as a higher lifetime within grains as may be deduced from the standard imaging technique. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Heinz and coworkers introduce an all‐photoluminescent, microscopic setup which may access the charge carrier lifetime in silicon reliably from nano‐ to milliseconds with micrometer spatial resolution using time‐correlated single photon counting. The application to high‐performance multicrystalline silicon reveals a more detrimental influence of small‐angle grain boundaries as well as a higher lifetime within the grains as may be deduced from the standard imaging techniques.